Ghana Agricultural Innovation and Data Hub (AIDH) - Wilson, Michael; Danquah, Paul; Awotwi, John; Sackey, Tracy (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The Ghana Agricultural Innovation and Data Hub (AIDH) builds on the achievements of the Ag-Data Hub from 2023 to create an integrated, decentralized, secure, and interoperable data exchange platform that seamlessly connects data providers and users within the agricultural sector. By establishing integration pathways with other national agricultural data portals and regional data exchanges, the platform aims to enhance collaboration and information sharing. The core focus is to support standardized data technologies that can drive innovative solutions, empowering stakeholders with the insights needed to make climate-smart decisions. Ultimately, this initiative seeks to foster data-driven innovations that promote sustainable agricultural productivity and resilience in the face of climate change.